The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1063/1.99353
|View full text |Cite
|
Sign up to set email alerts
|

Optical generation and detection of surface acoustic waves on a sphere

Abstract: Surface acoustic waves (SAW’s) have been optically generated and detected on metallic spheres. The source was a focused yttrium aluminum garnet (YAG) laser operated in the Q-switched mode and the probe was a sensitive optical heterodyne interferometer. The curvature of the surface gives rise to dispersive effects. The variation of the SAW group velocity is deduced from the evolving waveforms of pulses detected after propagating a few turns around the sphere. The observation of SAW pulse waveforms at positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…The ratio of any two strengths among the longitudinal, shear, and Rayleigh waves depends on Poisson's ratio. It is known that the spherical Rayleigh wave is dispersive due to the surface curvature [9]. As seen in Fig.…”
Section: Experimental Measurementsmentioning
confidence: 67%
See 2 more Smart Citations
“…The ratio of any two strengths among the longitudinal, shear, and Rayleigh waves depends on Poisson's ratio. It is known that the spherical Rayleigh wave is dispersive due to the surface curvature [9]. As seen in Fig.…”
Section: Experimental Measurementsmentioning
confidence: 67%
“…A similar study [9] reported measurements of Rayleigh waves generated on a sphere by a thermoelastic laser source and illustrated the general properties of this wave (e.g. the focusing at the poles and the wave dispersion).…”
Section: Experimental Measurementsmentioning
confidence: 92%
See 1 more Smart Citation
“…A point-by-point study of laser-generated surface phonons on a sphere was carried out by Royer et al [2]. Because of the application to ball devices based on surface acoustic waves, there is much interest in characterizing how surface phonons propagate on the surfaces of elastically isotropic or anisotropic spheres [3].…”
Section: Introductionmentioning
confidence: 99%
“…The profile of a circular wave front passing through a focus in 2D is known to undergo a shape change and a / 2 Gouy phase shift. 19,20 Our experimental resolution for ⌬ allowed us to study the former effect in detail but not the latter. The change in shape is governed by the complex value of the source function F 0 .…”
Section: ͑4͒mentioning
confidence: 99%